2019
DOI: 10.1021/acs.jced.9b00385
|View full text |Cite
|
Sign up to set email alerts
|

Solubility Determination, Correlation, and Solute–Solvent Molecular Interactions of 5-Aminotetrazole in Various Pure Solvents

Abstract: The purpose was to evaluate solubility data and solute–solvent molecular interactions of 5-aminotetrazole in various pure solvents including methanol, ethanol, n-propanol, isopropanol, 1-butanol, toluene, acetone, acetonitrile, ethyl acetate, 1,4-dioxane, N,N-dimethylformamide (DMF), and N-methyl pyrrolidone (NMP) at temperatures “T = 283.15–323.15 K” and pressure “P = 0.1 MPa”. Solubility data were determined by the isothermal saturation method with the help of high-performance liquid-phase chromatography. So… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…From Figure (c) and Table , the solubility order in the polar aprotic solvents was inconsistent with the sequences of solubility parameter, polarity, dipole moment, and dielectric constant. This indicated that the dissolution equilibrium of moroxydine hydrochloride was a complex phenomenon in the polar aprotic solvents which may be attributed to multi-influence factors, for instance, solvent properties, molecular sizes and shapes, steric effect, the interactions of solute–solvent, solvent–solvent, and solute–solute, etc. In addition, intersects between the solubility curves in polar aprotic solvents were found in Figure (c). This may be caused by the weight differences of the above factors at different temperatures. , …”
Section: Resultsmentioning
confidence: 93%
“…From Figure (c) and Table , the solubility order in the polar aprotic solvents was inconsistent with the sequences of solubility parameter, polarity, dipole moment, and dielectric constant. This indicated that the dissolution equilibrium of moroxydine hydrochloride was a complex phenomenon in the polar aprotic solvents which may be attributed to multi-influence factors, for instance, solvent properties, molecular sizes and shapes, steric effect, the interactions of solute–solvent, solvent–solvent, and solute–solute, etc. In addition, intersects between the solubility curves in polar aprotic solvents were found in Figure (c). This may be caused by the weight differences of the above factors at different temperatures. , …”
Section: Resultsmentioning
confidence: 93%
“…In addition, although the solubility of l -alanine in polar protic solvents was higher than that in polar aprotic solvents, the order in the two kinds of solvents was both inconsistent with the polarity, dipole moment, dielectric constant, and solubility parameter orders (the solvent properties can be seen in Table ). This indicated that the dissolution equilibrium of l -alanine was a complex phenomenon, which may be attributed to the comprehensive influence of various factors, such as solvent properties, molecular sizes and shapes, solute–solvent interactions, solvent–solvent interactions, solute–solute interactions, steric effect, etc. From Figure b, there were some intersects between the solubility curves, which may result from the weight differences of the above factors under different temperatures. , …”
Section: Resultsmentioning
confidence: 95%
“…The solubility of edaravone in (ethyl acetate + n -propanol), (acetonitrile + methanol), (acetonitrile + ethanol), and (acetonitrile + n -propanol) was determined by the isothermal saturation method. Four mixtures were prepared by using an analytic balance with the standard uncertainty of 0.0001 g. The mass fractions of ethyl acetate or acetonitrile in the mixtures varied from 0.2 to 0.8. The experimental process is the same as our previous studies, so it is only a simple description of the experimental steps.…”
Section: Methodsmentioning
confidence: 99%